Effects of different opioids on the contractile tension of isolated rat intestinal smooth muscle - Yang, Chen; Hu, Jianying; Cheng, Yan; Sun, Shen; Huang, Shaoqiang (Frontiers in Pharmacology, 2025)
BackgroudTo compare how five common opioids affect rat intestinal muscle tension and frequency across concentrations, establishing an animal model to provide translational evidence for selecting opioids with the least gastrointestinal impact.MethodsIsolated rat small intestine specimens were prepared, and six intestinal segments were selected from the same rat and placed into remifentanil, sufentanil, oxycodone, nalbuphine, butorphanol, and the control group with balanced solution. Experiments were carried out to observe and compare the changes in the contraction tension and contraction frequency of small intestinal smooth muscle during the change in concentration gradients of 10–9, 10–8, 10–7, 10–6, 10–5, and 10–4 M. Statistical analysis obtained from 10 rats in the in vitro intestinal tube experiment was performed.ResultsThe results revealed that when the concentration increased to 10−7 M, the intestinal contraction tension in the butorphanol group began to decrease significantly, and the intestinal contraction tension in the nalbuphine and oxycodone groups began to decrease significantly at concentrations of 10−6 M. while the sufentanil group and the remifentanil group showed a significant decrease in intestinal contractile tension at 10−5 M and 10−4 M, respectively. When the concentration of the drug increased to 10−4 M, the contraction frequency of the sufentanil group decreased significantly, and there was no statistical difference among concentrations of other drugs.ConclusionAs the concentration increased, different opioids inhibited the contractile tone of rat intestinal smooth muscle in vitro. The intensity of inhibition was butorphanol > nalbuphine ≈ oxycodone > sufentanil > remifentanil, and the Contraction frequency was almost unaffected except in the very high concentration sufentanil group.